Parental hesitancy on COVID-19 vaccination of children under the age of 16: A cross-sectional mixed-methods study among factory workers - Kyaw Thiha Aung; Ye Minn Htun; Zin Lin Htet; Yan Naing Myint Soe; Phyo Ko Ko; Win Oo; May Soe Aung; Tun Tun Win (PLoS ONE, 2025)
Background Thanks to the development of COVID-19 vaccines, now they can be safely and effectively used to guard COVID-19 patients against severe illness, hospitalization, and even mortality. However, parents’ unwillingness to vaccinate their children depends on a large extent on factors beyond the availability of vaccines, and understanding the factors associated with parental vaccine hesitancy has become increasingly important to the development of the COVID-19 vaccine program. Therefore, this study aimed to determine the parental COVID-19 vaccine hesitancy to their children and its associated factors among factory workers in Myanmar. Methods A cross-sectional mixed-methods study was conducted as an explanatory sequential design, at Tri Star tyre factory (Ywar Ma), Yangon, Myanmar from August 2022 to February 2023. A total of 170 factory workers with children under the age of 16 participated in this study. The quantitative data were collected by the face-to-face interviews using a pretested structured questionnaire that included the Oxford COVID-19 vaccine hesitancy scale. Data were analyzed by using binary logistic regression to identify associated factors of parental hesitancy. Adjusted odds ratio (AOR) with a 95% confidence interval (CI) was computed to determine the level of significance with a p value ≤ 0.05. A subsample of 6 participants from each “hesitant group” and “non-hesitant group” towards COVID-19 vaccination was interviewed by the individual in-depth-interview guide to provide the reasons for their willingness or unwillingness to vaccinate to their children. The thematic analysis was undertaken for the qualitative data. Results Among the total, 18.2% (95% CI: 12.7–24.9%) of the parents were hesitant to vaccinate their children against COVID-19 while 25.9% (95% CI: 19.5–33.1%) responded as unsure and 55.9% (95% CI: 48.1–63.5%) were non-hesitant for vaccination to their children. Male (AOR: 3.04, 95% CI: 1.35–6.84) and those who were not infected with SARS-CoV-2 (AOR: 2.66, 95% CI: 1.06–6.70) were significantly associated with parental COVID-19 vaccine hesitancy. The most common reasons for the unwillingness to receive the COVID-19 vaccination to their children were too young for vaccination, concerns about the safety of the vaccines, uncertainty about the effectiveness of the vaccines, and lack of trust in the origin of the vaccines. Conclusions In this study, nearly one-fifth of the parents were hesitant to vaccinate their children against COVID-19. The findings of this study suggested that the government and healthcare professionals should provide health education about the importance of COVID-19 vaccination and the safety and efficacy of currently providing COVID-19 vaccines using mainstream media to improve the proportion of children getting vaccinated against COVID-19.